The MOI impact framework: a catalyst for systemic change in museums - Hamari, Pirjo; Runnel, Pille; Uusikylä, Petri; Aljas, Agnes (Frontiers media, 2026)
This article examines a practice-based approach to museum development in the context of the growing necessity for systemic change in contemporary museum practice, adding to current debates in museum and cultural management studies on organisational change and impact. As museums operate in increasingly complex environments, they are expected not only to manage internal processes but also to demonstrate social impact and public value. From this perspective, the article outlines three interrelated approaches to museum development: managerial, audience-centred, and systemic. These are positioned as a conceptual framework through which the article presents the “Museums of Impact” (MOI) framework (MOI Framework). As opposed to traditional evaluation models focused on external assessment and performance measurement, the MOI framework is designed as an internally driven, developmental tool that supports organisational learning and change. Building on an abductive, co-creative process involving museum professionals across Europe into building a tool and a secondary research phase, the MOI framework is introduced as an approach to organisational self-evaluation that supports reflective dialogue and impact-oriented development. Drawing on developmental evaluation and systems thinking, the framework merges strategic, participatory, and structural dimensions of change. The article discusses the framework as a tool for organisational learning and internal development, and considers its relevance for supporting systemic approaches to change within the museum sector.
Keywords: museum management; organisational learning; self-evaluation; societal impact; systems thinking; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|